2021
DOI: 10.17219/acem/121927
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of evaluation of collateral circulation in short-term prognosis of wake-up stroke patients

Abstract: Background. In recent years, the clinical significance of collateral circulation in vascular embolism has been gradually found.Objectives. To investigate the relationship between collateral circulation and short-term prognosis of wakeup stroke patients. Materials and methods.The present observational study enrolled 269 cases of wake-up ischemic stroke patients. All patients presented with mismatched low perfusion volume/main infraction volume and received thrombolytic therapy after admission. The hemorrhagic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous meta-analysis showed that patients with better collateral circulation could have a smaller ischemic core on perfusion and less severe neurological symptoms at baseline and have a better chance of achieving a favorable or excellent functional outcome at 3 or 6 months after the index stroke ( 18 ). Another study ( 14 ) used CTA for WUS evaluation and found that collateral circulation condition graded by the ASITN/SIR was an independent risk factor for bad prognosis of wake-up ischemic stroke patients in 3 months. In this study, we found good collateral circulation (2–3 score) was a strong predictor for good outcome in WUS with relatively larger AUC than the penumbra volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous meta-analysis showed that patients with better collateral circulation could have a smaller ischemic core on perfusion and less severe neurological symptoms at baseline and have a better chance of achieving a favorable or excellent functional outcome at 3 or 6 months after the index stroke ( 18 ). Another study ( 14 ) used CTA for WUS evaluation and found that collateral circulation condition graded by the ASITN/SIR was an independent risk factor for bad prognosis of wake-up ischemic stroke patients in 3 months. In this study, we found good collateral circulation (2–3 score) was a strong predictor for good outcome in WUS with relatively larger AUC than the penumbra volume.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies proposed different imaging evaluation criteria for WUS (11)(12)(13)(14). One study (11) suggested that WUS should be evaluated by using the ratio of ischemic penumbra to hypo-perfusion area >50% on CTP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation